Analisis effisiensi dan pendapatan usahatani tebu dan usahatani padi pada lahan sawah beririgasi di Kabupaten Bantul = (Farmers Income and Efficiency Analysis of Sugarcane and Rice Farms on Irrigated land in Bantul - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
The objectives of this study are (1) to know and compare the efficiency of sugarcane and rice farms on irrigated area, (2) to know the labor used efficiency of both sugarcane and rice farms and (3) to estimate per hectare farm income of both sugarcane and rice farms. Data were gathered by survey and interview to farmers and fanner groups sample. For sugarcane farm, 60 farmer groups were selected 30 groups of the first planting sugarcane (TRISUS-I) and 30 groups of the first ratoon (TRISUS-I). At the same area, 30 rice farmers were selected randomly as the sample. Frontier production function was estimated to measure technical efficiency of both rice and sugarcane farm. While everage production function was estimated to know economic efficiency of inputs use. Both sugarcane and rice farm in this study have not been technically efficient as indicated by the TER coeficient which is less than 1. However sugarcane farm is more technically efficient. In term of economic efficiency, the used of inputss for this kind of farm also have not been efficient, indicated by value marginal product which is greater then price of inputs. To increase fanner income, it is suggested to give opportunity to the farmers in selecting their comodities. To meet domestic sugarcane consumption effort of increasing sugarcane production could be done in dry land areas.